Treatment effect, postoperative complications, and their reasons in juvenile thoracic and lumbar spinal tuberculosis surgery - He, Qing-Yi (J Orthop Surg Res, 2015)
OBJECTIVE: Fifty-four juvenile cases under 18 years of age with thoracic and lumbar spinal tuberculosis underwent focus debridement, deformity correction, bone graft fusion, and internal fixation. The treatment effects, complications, and reasons were analyzed retrospectively. MATERIAL AND METHOD: There were 54 juvenile cases under 18 years of age with thoracolumbar spinal tuberculosis. The average age was 9.2 years old, and the sample comprised 38 males and 16 females. The disease types included 28 thoracic cases, 17 thoracolumbar cases, and 9 lumbar cases. Nerve function was evaluated with the Frankel classification. Thirty-six cases were performed with focus debridement and deformity correction and were supported with allograft or autograft in mesh and fixed with pedicle screws from a posterior approach. Eight cases underwent a combined anterior and posterior surgical approach. Nine cases underwent osteotomy and deformity correction, and one case received focus debridement. The treatment effects, complications, and bone fusions were tracked for an average of 52 months. RESULTS: According to the Frankel classification, paralysis was improved from 3 cases of B, 8 cases of C, 18 cases of D, and 25 cases of E preoperatively. This improvement was found in 3 cases of C, 6 cases of D, and 45 cases of E at a final follow-up postoperatively. No nerve dysfunction was aggravated. VAS was improved from 7.8 ± 1.7 preoperatively to 3.2 ± 2.1 at final follow-up postoperatively. ODI was improved from 77.5 ± 17.3 preoperatively to 28.4 ± 15.9 at final follow-up postoperatively. Kyphosis Cobb angle improved from 62.2° ± 3.7° preoperatively to 37° ± 2.4° at final follow-up postoperatively. Both of these are significant improvements, and all bone grafts were fused. Complications related to the operation occurred in 31.5 % (17/54) of cases. Six cases suffered postoperative aggravated kyphosis deformity, eight cases suffered proximal kyphosis deformity, one case suffered pedicle penetration, one case suffered failure of internal devices, and one case suffered recurrence of tuberculosis. CONCLUSION: As long as the treatment plan is fully prepared, the surgical option can achieve a satisfactory curative effect in treating juvenile spinal tuberculosis despite some complications.